2018
DOI: 10.1101/333245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying individual risk rare variants using protein structure-guided local tests (POINT)

Abstract: Rare variants are of increasing interest to genetic association studies because of their etiological contributions to human complex diseases. Due to the rarity of the mutant events, rare variants are routinely analyzed on an aggregate level. While aggregation analyses improve the detection of global-level signal, they are not able to pinpoint causal variants within a variant set. To perform inference on a localized level, additional information, e.g., biological annotation, is often needed to boost the informa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…We test the structure kernel approach implemented in POKEMON and compare it to two other structure-informed association methods, PSCAN and POINT (Tang et al 2020;Marceau West et al 2019) and a frequency-based kernel analogous to a SKAT analysis of missense variants (Figure 1). We evaluated the false positive rate (FPR) of POKEMON with the structure kernel and found that the averaged FPR is 0.0455 for all simulated configurations (Supplemental Fig…”
Section: Pokemon Can Detect Associations With Spatially Clustered or ...mentioning
confidence: 99%
“…We test the structure kernel approach implemented in POKEMON and compare it to two other structure-informed association methods, PSCAN and POINT (Tang et al 2020;Marceau West et al 2019) and a frequency-based kernel analogous to a SKAT analysis of missense variants (Figure 1). We evaluated the false positive rate (FPR) of POKEMON with the structure kernel and found that the averaged FPR is 0.0455 for all simulated configurations (Supplemental Fig…”
Section: Pokemon Can Detect Associations With Spatially Clustered or ...mentioning
confidence: 99%